Neutron-capture measurement candidates for the r-process in neutron star mergers - Vescovi, Diego; Reifarth, René; Cristallo, Sergio; Couture, Aaron (Frontiers in Astronomy and Space Sciences, 2022)
Neutron star mergers (NSMs) are one of the astrophysical sites for the occurrence of the rapid neutron capture process (r-process). After a merger, the ejected neutron-rich matter hosts the production of radioactive heavy nuclei located far from the stability valley. Their nuclear physics properties are key inputs for r-process nucleosynthesis calculations. Here we focus on the importance of neutron-capture rates and perform a sensitivity study for typical outflows from NSMs. We identify the rates with the highest impact on the final r-process abundance pattern and the nuclear energy release, therefore determining the nucleosynthesis in NSMs. A list of major n-capture rates affecting individual isotopes and elements production is also provided.